2020
DOI: 10.1111/joor.13034
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical panel of degenerated articular discs from patients with temporomandibular joint osteoarthritis

Abstract: Background Temporomandibular joint osteoarthritis (TMJOA) is a progressive degenerative disease caused by imbalance between anabolic and catabolic stimuli. Objective The aim of this study was to evaluate histopathological changes, collagen degeneration and the expression of eleven TMJOA biomarkers in articular discs. Methods Specimens were obtained from eight female patients submitted to discectomy. Discs were divided into anterior band (AB), intermediate zone (IZ) and posterior band (PB) for computerised hist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…In the pilot human clinical trial, we demonstrated that MoFi-processed PBMNCs effectively ameliorated pain and stiffness in OA patients. The administration of the PBMNCs might prohibit the inflammatory response of synovial tissues by suppressing IL-1, TNF-α, and C-reactive protein (CRP) expression and decreasing bone marrow lesions or edema (BML/BME) and synovitis even at the late stage of KOA 23 , 24 . The validation of the anti-inflammatory effects of PBMNCs injection in humans requires further magnetic resonance imaging (MRI) to examine the reduced knee synovitis and BML at 1 year and 2 years post-treatment 25 , 26 .…”
Section: Discussionmentioning
confidence: 99%
“…In the pilot human clinical trial, we demonstrated that MoFi-processed PBMNCs effectively ameliorated pain and stiffness in OA patients. The administration of the PBMNCs might prohibit the inflammatory response of synovial tissues by suppressing IL-1, TNF-α, and C-reactive protein (CRP) expression and decreasing bone marrow lesions or edema (BML/BME) and synovitis even at the late stage of KOA 23 , 24 . The validation of the anti-inflammatory effects of PBMNCs injection in humans requires further magnetic resonance imaging (MRI) to examine the reduced knee synovitis and BML at 1 year and 2 years post-treatment 25 , 26 .…”
Section: Discussionmentioning
confidence: 99%
“…The temporomandibular joint (TMJ) disc cushions and redistributes the mechanical load on condyles during mandibular movements (Tanaka & van Eijden, 2003). Degenerative joint disease of the TMJ is common and affects 17.97%–77.23% of patients with TMJ disorders (Pantoja et al, 2019; Valesan et al, 2021); it is characterized by the release of inflammatory cytokines and overexpression of catabolic biomarkers, such as matrix metalloproteinases (MMPs) (Fernandes et al, 2020; Leonardi et al, 2007). Local inflammation damages the micro‐environment around TMJ disc cells and deteriorates the TMJ disc ultrastructure and its nanomechanical properties (Cui et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…biomarkers, such as matrix metalloproteinases (MMPs) (Fernandes et al, 2020;Leonardi et al, 2007). Local inflammation damages the micro-environment around TMJ disc cells and deteriorates the TMJ disc ultrastructure and its nanomechanical properties (Cui et al, 2019).…”
mentioning
confidence: 99%